PENGARUH SPIRITUAL LEADERSHIP DAN WORK LIFE BALANCE TERHADAP KINERJA PERAWAT DIMEDIASI OLEH KEPUASAN KERJA - Fitri, Hirzatul; Munthe, Richa Afriana; Sofiyanti, Efrita (Ekomania, 2024)
This study aims to determine the influence of spiritual leadership and work-life balance on performance through employee job satisfaction at Tengku Rafi'an Regional Hospital, Siak Regency. The research method used is quantitative research. The sample in this study were 132 nurses at Tengku Rafi'an Regional Hospital, Siak Regency. The data collection technique used was a structured questionnaire. The instrument testing technique in this study was the validity and reliability test using PLS (Partial Least Square) as the measurement. The results of this study indicate that there is. Spiritual leadership does not have a significant effect on nurse performance, while work-life balance and job satisfaction have a positive effect on nurse performance. Spiritual leadership and work-life balance have a positive effect on nurse job satisfaction. Spiritual leadership and work-life balance have a positive effect on nurse performance mediated by job satisfaction